(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This review article mainly focuses on the advanced technology of isokinetic exercises which will help to increase range of motion, strength of muscles, endurance and many more advantages. These are the resistive machines which promote to bring back normal movements of a person daily life with significant results. Its advantage is that the group of muscles may be worked out at its maximum potential throughout a range of motion of joint. Different devices which promote resistance are studied in this article. Objective : To determine the evidence of rehabilitation by using ERIK , isokinetic dynamometer in lower limb.